AB1020 High Prevalence of BF% Obesity in Chinese Patients with Rheumatoid Arthritis: A Cross-Sectional Study. (15th July 2016) - Lin, J.-Z.; Chen, Y.-B.; Lin, X.-T.; Ma, J.-D.; Mo, Y.-Q.; Wang, X.-Y.; Dai, L.
Abstract : Background: There is about 14%–19% lipid of weight in normal people and most of the lipid stores in fat cells that can secrete adipokines to promote inflammation, which may exacerbate rheumatoid arthritis (RA) synovial inflammation, rise severity of clinical feature, disable functional capacity and reduce quality of life. A worldwide study in 15 countries (mainly in Europe and the United States) identified 18% of RA patients as obese defined by body mass index (BMI ≥30 kg/m 2 ), while higher prevalence of 25% in a USA-based study and 31% in a UK–based study were reported. However, little is known about the prevalence of obesity in Chinese RA patients. Objectives: To investigate the prevalence and character of obesity in Chinese RA patients. Methods: Two hundred and forty–seven consecutive RA patients were assessed BMI, waist circumference (WC), waist–to–hip ratio (WHR) and waist–to–height ratio (WHtR). Clinical data including RA disease activity, physical function and complications were collected. Body fat percentage (BF%) was assessed by bioelectric impedance and obesity by BF% was defined as >25% for men and >30% for women. Results: (1) According to Chinese criteria of BMI, there were 19% patients with overweight and 5% with obesity. According to BF%, there was 52% patients with obesity and female RA patients had significantly higher prevalence of obesity than male patients (55% vs 31%, P=0.006, Figure 1 ). (2) Weight, total fat mass and trunk–to–appendicular fat ratio (TAFR) were significantly higher in BF% obesity patients than normal ones (all P<0.05). The percentages of patients whose fat distributed mainly in trunk rather than appendicular extremities (TAFR >1) was also higher in BF% obesity patients than normal ones (83% vs 43%, P<0.001, Table 1 ). (3) According to WC, WHR and WHtR, there were 33%, 41% and 42% patients with central obesity respectively. The trunk-fat-to-weight percentage (TfW%) was significantly higher in central obesity patients (according to WC in Chinese criteria) than that in normal WC patients (female: 18.7% (16.6%–19.8%) vs 13.6% (11.0%–15.7%); male: 15.0% (12.4%–18.3%) vs 7.4% (3.8%–10.6%), both P<0.001). ROC curve analysis showed that the cut–off value of the TfW% for diagnosing central obesity was 11.8% in men with sensitivity 91.7% and specificity 87.5% and 16.3% in women with sensitivity 81.2% and specificity 83.1% (male: AUC=0.941, 95%CI: 0.868–1.0; female: AUC=0.865, 95%CI: 0.811–0.919, both P<0.001). There were 95 (38%) patients with central obesity according to the cut–off value of the TfW% (female 38% and male 39%, Figure 1 ). (4) Comparing with normal BF% patients, BF% obesity patients were older with higher disease activity indicators (ESR and CRP) and had more complications such as dyslipidemia and fat liver (all P<0.05, Table 1 ). Conclusions: This cross–sectional study suggests that high prevalence of BF% obesity in Chinese RA patients especially in female patients which might be associated with disease activity. Acknowledgement: This work was supported by National Natural Science Foundation of China (81471597), Specialized Research Fund for the Doctoral Program of Higher Education (20130171110075) and Guangdong Natural Science Foundation (2014A030313074). Disclosure of Interest: None declared